YouTube-Assisted Self-Regulated Vocabulary Learning: Indonesian EFL Learners’ Experiences - Suli, Mad; Kamil, Acep Bahrum; Mobit, Mobit (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research is aimed to explore students’ YouTube-assisted vocabulary learning in the self-regulated learning context. This research was conducted with the participants of four students from a vocational high school in Karawang. This research used narrative inquiry approach; thus, the data were collected through interview, specifically semi-structured interview. The data of this research were analysed by thematic analysis method. This research has discovered that students would start to learn when they had spare time to use, they also had to keep on eye to the internet connection during their learning process, and lastly, they tried to recall the vocabulary they just learned after they finished their learning. Students also had some criteria for the videos they watched in their learning process. This research also found that students experienced some enjoyments in their YouTube-assisted vocabulary learning, although they were still reluctant to continue their learning.